ISOLATION, IDENTIFICATION AND PHYLOGENETIC CHARACTERIZATION OF POTASSIUM-SOLUBILIZING RHIZOBACTERIA ISOLATED FROM THE ROOTS OF Mimosa indica WEED - Nwokeh, U. J.; Okoro, I. G.; Orodeji, C. U. (FUDMA JOURNAL OF SCIENCES, 2022)
Most microorganisms residing within plant rhizosphere are of great importance to soil fertility.  The either release plant nutrient into soil solution and make it available for plant absorption directly or indirectly, excrete enzymes or organic acids that facilitate the solubilization of insoluble minerals, such as potassium (K). A laboratory analysis was carried out at the Soil Science Laboratory in Michael Okpara University of Agriculture, Umudike, to isolate potassium-solubilizing rhizobacteria from Mimosa indica a weed that have invaded most agricultural land in the southeastern Nigeria. It was observed that the roots of Mimosaindica had nodules, which is peculiar to legume plants. Two cultivable isolates possessed the ability to solubilize K.  DNA extraction was done and the two bacteria were identified as: Ochrobactrum anthropi and Comamonas testosteroni.  Biochemical tests and Phylogenetic characterization were carried out. Comamonas testosterone gave the highest solubilization efficiency of 650 compared to Ochrobactrum anthropi (325).
Keywords: DNA Extraction; Mimosa indica; Plant-growth promoting rhizobacteria; Potassium-solubilizing rhizobacteria; Solubilization efficiency